Clinical Characteristics and Outcome of Kidney Transplant Recipients Infected with COVID-19: A Retrospective Observational Study - Manzoor Ahmad Parry; Rayees Yousuf Sheikh; Raja Kaamil Qadri; Muzafar Maqsood Wani; Imtiyaz Wani; Mohammad Ashraf Bhat (Indian Journal of Transplantation)
Background: This study investigated the clinical characteristics and outcomes of kidney transplant recipients (KTRs) who contracted COVID-19. Methods: In this retrospective study, we analyzed data from 122 KTRs confirmed to have COVID-19. Results: The mean age in patients with mild COVID-19 disease was 37.1 ± 9.1 years, whereas those with moderate and severe disease were 44.7 ± 13.7 and 48.1 ± 11.2 years, respectively (P = 0.02). The median neutrophil-to-lymphocyte ratio was 4.2 (interquartile range [IQR] 3.0–6.8) for mild cases, 6.5 (IQR: 5.0–10.8) for moderate cases, and 19 (IQR: 7.0–24.7) for severe cases (P = 0.008). The median C-reactive protein (CRP) levels (mg/L) were 19.5 (1QR: 5.0–156.3), 53.9 (1QR: 31.5–96.0), and 63.4 (1QR: 23.2–228) for mild, moderate, and severe cases, respectively (P = 0.006). Acute kidney injury occurred in 13.6%, 60%, and 81.57% of patients with mild, moderate, and severe cases, respectively (P = 0.004). Risk factors for a composite outcome of death and dialysis included age >50 years (odds ratio [OR]: 3.25, confidence interval [CI]: 1.25–7.7; P = 0.027), nonvaccinated status (OR 2.87, CI: 1.56–4.18; P = 0.008), graft dysfunction (OR: 2.1, CI: 1.2–5.9; P = 0.034), and CT severity index (CTSI) >13 (OR 3.3, CI: 1.5–5.9; P = 0.040). Conclusions: COVID-19 infection in KTRs is linked to a high mortality rate. Advanced age, lymphopenia, elevated CRP levels, and acute graft dysfunction are associated with disease severity. Age >50 years, nonvaccinated status, graft dysfunction, and a CTSI >13 are risk factors for the composite outcome of death and dialysis.